Climate change and its impact on cotton (Gossypium sp.) - SANKARANARAYANAN, K; PRAHARAJ, C S; NALAYINI, P; BANDYOPADHYAY, K; GOPALAKRISHNAN, N (The Indian Journal of Agricultural Sciences, 2010)
The earth temperature has increased by 0.74°C during the last century (1906 to 2005) due to increase in greenhouse gases through anthropogenic emissions as reported by IPCC. Thus, the increase in temperature is likely to be 1.8–4.0°C by the turn of 21st century resulting in anticipated greater instability in food, feed and fibre production. Increase in temperature can reduce crop duration, change pest populations, hasten mineralization in soils and increase evapotranspiration. It is reported that 40 and 50% less biomass is anticipated in cotton (Gossypium sp.) at 20/10°C and 40/30°C, respectively, with optimum temperature of 30/20°C. However, increase in atmospheric CO2 increases the quantum of yield produced photosynthetically, net photosynthesis, biomass production and ultimate output. Besides higher output, increasing inputs-use efficiency in cultivated crops is also realized and the same at much greater pace in C3 plants (cotton). Study showed that increase in seed cotton yield up to 43% was realized at elevated CO2 of 550 ppm throughout the crop-growing period. Severe sucking pest problem and dominance of weeds are expected in cotton. Thus, in total, elevated CO2 favours cotton growth and yield but higher temperature influences these negatively. The effect of climate change on national cotton production system interpreted that increasing CO2 concentration could help to increase cotton production in all the 3 zones. However, increasing precipitation with decreasing temperature may prolong the vegetative growth and extend the crop duration, which pose difficulties in timely sowing of succeeding rabi crops in north zone. The expected increasing of temperature, decreasing rainfall with erratic distribution in central and south zone leads to frequent wet and dry spell with high evapotranspiration demands. Prolonged dry spell during critical crop growth periods may affect yield. The projected waterlogging coupled with drought by increasing intensity of rainfall may further induce reddening in Bt cotton. Shortening of crop growth periods induced by increasing temperature may facilitate to fit cotton crop into rice (Oryza sativa L.)–fallow cotton system in south zone. Cotton belongs to the C3 plant, which releases CO2 during photorespiration. High external input and overuse of N fertilizers lead to more emission of nitrous oxide. The mitigation strategies should aim to reduce inorganic inputs utilization with more emphasis to nitrogen includes following of integrated nutrient management practice, use of N-fixing Azotobacter and Azospirillum, legumes rotation, application of slow-release nitrogenous fertilizers, adoption of drip-fertigation, incorporation of cotton stalk could reduce fertilizer nitrogen usage. It is evident that application of farmyard manure, mulching greengram (Vigna radiata L. Wilczek), glyricidia sp. and sunnhemp (Crotolaria juncea L.) as green manure recorded 15–32% increase in yield over control and there was considerable build-up of soil available nutrients. Cotton crops grown in future environments will be subjected to a climate for which they are not bred. Cotton species of G. barbadense showed more sensitive than G. hirsutum. G. arboreum is suitable for low and erratic rainfall with drought situations. In saline environment G. herbaceum showed better adaptability. The available drought tolerance hirsutum genotypes, like ‘LRA 5166’, ‘KC 2’ and ‘AKH 081’ may show better adaptation. The risk and uncertainty imposed by climate change could be managed by adoption of location-specific intercropping and multi-tier cropping system. In situ soil moisture conservation techniques include contour bunding, graded, narrow or broad ridges or beds separated by furrows, ridges and furrow, opening of furrow after every rows of cotton, black polythene mulch (25 microns), and spreads of crop residue were found to be promising